Waste to wealth : Alternative source of glycosaminoglycans (GAGs) from sea food waste - Nurul Haida, Idrus; Nina Suhaity, Azmi; Jaya Vejayan, Palliah (The Institute of Integrative Omics and Applied Biotechnology, 2016)
Glycosaminoglycans (GAGs) are compounds that were used to treat various diseases. Generally GAGs widely used in biological and medical approaches. Osteoarthritis (OA) is the one example of disease that used GAGs by enhancing the production of cartilage matrix components in the joints. In Malaysia, management of organic waste such as fish bone is the focus point to achieve environmental sustainability. Sea food waste from Lates calcarifer was used as the model to extract GAGs where a few tests were carried out to verify the presence of GAGs. These fish is popularly sought-after and this will provide its unwanted parts (gills and viscera) into therapeutically and economically viable solution for society. Then, the invention convert this waste to wealth which help for the better utilization of seafood waste. Analytical testing were carried out to determine the similarity of the functional group that were presence in sample with standard provided. Instead of that, Blyscan assay kit was used to determine the presence of GAGs in crude sample. From the result obtained, GAGs are well distributed in sea food waste of Lates Calcarifer. Instead of that, waste management can be minimize by convert waste to wealth product.